Morphological changes in distant muscle fibers following thermal injury in Wistar rats - Oliveira,Flavia de (2010)
PURPOSE: Thermal injury causes catabolic processes as the body attempts to repair the damaged area. This study evaluated the effects of a scald injury on the morphology of muscle fibers belonging to a muscle distant from the lesion. METHODS: Thirty Wistar rats were divided into control (C) and scalded (S) groups. Group S was scalded over 45% of the body surface, standardized by body weight. Rats in both groups were euthanized at four, seven and 14 days following the injury. The middle portions of the medial gastrocnemius muscles were sectioned, stained with hematoxylin and eosin and Picrosirius, and submitted to histological analysis. RESULTS: Control group sections exhibited equidistantly distributed polygonal muscle fibers with peripheral nuclei, characteristic of normal muscle. The injured group sections did not consistently show these characteristics; many fibers in these sections exhibited a rounded contour, variable stain intensities, and greater interfiber distances. A substantially increased amount of connective tissue was also observed on the injured group sections. CONCLUSION: This experimental model found a morphological change in muscle distant from the site of thermal injury covering 45% of the body surface.